Biotechnological prospecting for copper recovery in electro-electronic waste (memory board) - Alves , Marcely Figueiredo; Lima, Sidney Marlon Lopes de; Campos-Takaki, Galba Maria; Andrade, Rosileide Fontenele da Silva (Seven Editora, 2023)
The recovery of Electro-electronic Waste (EER) is linked to the fifteenth goal of the Sustainable Development Goals (SDGs) which aims to recover and promote the sustainable use of terrestrial ecosystems. One of the main components of waste electrical and electronic equipment is the printed circuit board (PCIs)-(Motherboard) which has in its composition valuable metals that can be recovered including copper. In this context, the aim of the present study was to investigate the potential of bioleaching of bacteria in the recovery of copper in the disposal of Printed Circuit Boards (PCIs). Three bacteria (Bacillus subtilis  UCP 1594, Pseudomonas fluorescens  UCP 1514 and Geobacillus stearothermophilus UCP  1520) were used. Initially, the bacteria were acclimatized in PCIs crushed into small particles and then they were transferred to AN medium (nutrient agar) added of 0.02g, 0.08g and 0.1g. L of crushed PCIs. Then, the acclimatized bacteria were submitted to the bioleaching process. The bioleaching process occurred in T&K medium added to a 2 cm PCI, in addition to the inoculum of 10% (107CFU/mL). The process occurred under orbital agitation  of 180rpm, during 15 days and 37ºC. The identification of the potential of the bacteria in the removal of copper from the PCIs was evaluated through electrical conductivity, atomic absorption, Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). According to the results obtained, all bacteria grew in solid medium at the maximum concentration of PCIs tested (0.1g/L) with an uncountable number of colonies. In addition, the maximum concentration (18.98 S/m, 17.58 S/m and 17.31 S/m,) of electrolytes in the bioleached solution occurred after 15 days of cultivation of Pseudomonas fluorescens, Geobacillus stearothermophilus and Bacillus subtilis, respectively. The bacterium with the greatest potential to extract copper from PCIs was Geobacillus stearothermophilus with recovery of 13.9% of the copper adsorbed in the biomass. In addition, from the results of scanning electron microscopy - SEM it was possible to evidence the formation of corrosion pits by all strains studied. Therefore, the bacterium Geobacillus stearotermophillus showed promise for copper extraction from WEEE with economic potential to stimulate the reuse and reinsertion of metallic copper in the production chain, contributing to the circular economy, sustainability and recycling of electrical and electronic waste. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-169